2019
DOI: 10.3389/fphar.2019.00686
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba Extract Modulates the Retroperitoneal Fat Depot Proteome and Reduces Oxidative Stress in Diet-Induced Obese Rats

Abstract: The rapid increase in the number of individuals with obesity, over the past four decades, is triggered by a number of complex interactions among factors. Despite the plethora of treatments available, side effects are commonly observed and, in this context, herbal medicines have been employed as an alternative form of therapy. Ginkgo biloba extract (GbE) has been described as a promising new pharmacological approach to treat obesity. In order to better comprehend the mechanisms involved w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 86 publications
2
19
0
Order By: Relevance
“…Since no alterations were observed in the protein levels of POMC, 5-HT1B, and 5-HT2C, neither in food intake nor in body mass, we hypothesize that the GbE hypophagic activity might occur after a prolonged GbE supplementation. Indeed, this hypothesis is aligned with previous studies from our group in which the GbE 14-day supplementation reduced food intake, body weight gain, and visceral adiposity in DIO rats [15,16,18]. We have also reported that GbE modulated hypothalamic and hippocampal anorexigenic mechanisms after a 14-day treatment protocol, supporting a hypothesis for a time-…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Since no alterations were observed in the protein levels of POMC, 5-HT1B, and 5-HT2C, neither in food intake nor in body mass, we hypothesize that the GbE hypophagic activity might occur after a prolonged GbE supplementation. Indeed, this hypothesis is aligned with previous studies from our group in which the GbE 14-day supplementation reduced food intake, body weight gain, and visceral adiposity in DIO rats [15,16,18]. We have also reported that GbE modulated hypothalamic and hippocampal anorexigenic mechanisms after a 14-day treatment protocol, supporting a hypothesis for a time-…”
Section: Discussionsupporting
confidence: 90%
“…It is possible that the beneficial effects of GbE on glucose and cholesterol metabolism, insulin signaling, visceral adiposity, and energy homeostasis previously observed in both the DIO [15,16] and ovariectomized rats [20] might be related to the early modulation of the POMC pathway (Figure 5). dependent hypophagic effect [17][18][19][20][21]. That the effect is time-dependent was also suggested in studies evaluating the modulation of memory.…”
Section: Discussionmentioning
confidence: 84%
“…Studying diet-induced obese rats, we have demonstrated both anti-oxidant and anti-inflammatory roles for GbE, along with improvement of insulin signaling in gastrocnemius muscle and retroperitoneal adipose tissue. GbE also had an anti-obesogenic effect and improved the lipid profile 21 24 .…”
Section: Introductionmentioning
confidence: 93%
“…The leaves and seeds of this plant have been used for medicinal purposes in China for centuries, initially being used for asthma and problems in the digestive system. In Europe and the USA, they have been sold since the sixties, and now they represent one of the most popular phytotherapeutic products in the world [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%